Formulation and Evaluation of Typhonium flagelliforme Tuber Extract Tablets with Cytotoxic Activity Against MCF-7 Breast Cancer Cells - Dede Komarudin; Yulis Adriana (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2026)
Cancer is the leading cause of death. Data from the Global Cancer Observatory shows that in 2022, Breast cancer in women ranks second and is the leading cause of death. Because of the limited cancer treatments available, medicinal plants are an alternative because they have anticancer properties. The indigenous Indonesian medicinal plant Typhonium flagelliforme has been widely used in various studies for its potential as an anticancer. Currently, medicinal plants are generally used in capsules, which are more sensitive to moisture and temperature that can affect drug stability compared to tablets. The aim of this research was to produce tablets containing active extract from Typhonium flagelliforme that meet physical quality requirements as anti-breast cancer tablets with cytotoxic activity against MCF-7. The research method is in vitro test of cytotoxic activity against MCF-7 cells. The results of the research   show that ethanol extract from Typhonium flagelliforme tubers can be formulated into tablets that have potential as a breast cancer treatment. Ethanol extract is the most active extract with an IC50 value of 16.04 µg/mL in MCF-7 cells. The physical parameters extract granules from Formulas 1 to 3 meet the requirements. The physical parameters of tablets in Formulas 1 to 3 meet the requirements, but the disintegration time of Formula 3 tablets does not meet the requirements.Keywords: Breast cancer, MCF-7, Tablet, Typhonium flagelliforme, Physical parameters of the tablet